Expression of stress-related proteins in Sediminibacterium sp. growing under planktonic conditions - Ayarza, Joaquín M. (2015)
Aggregation is a common trait of bacteria in natural and engineered biological systems. Microbial aggregates, such as flocs, granules, and biofilms, are spatially heterogeneous environments. It is generally observed that by growing under aggregated conditions bacteria respond and adapt to environmental stress better than free-swimming bacteria of the same species. We performed a proteomic analysis of a strain of Sediminibacterium, isolated from activated sludge, which grew planktonically in diluted culture media and in an aggregated form in media containing a high concentration of organic substrate. Auto-aggregation was also observed in the presence of pyruvate in dilute media. Expression of a number of stress-related proteins significantly increased under planktonic growth in comparison to aggregate growth. The upregulated proteins, identified by MALDI-TOF mass spectrometry, were two isoforms of a protein belonging to the universal stress family (UspA), a thioredoxin-disulfide reductase, the Campylobacter jejuni orthologue transcriptional regulator (Cj1172c), and the CocE/NonD hydrolase. We conclude that Sediminibaterium sp. C3 growth is stressed under planktonic conditions and that aggregation induced by pyruvate protects the bacteria against oxidative stress.